ANALISIS KEBIJAKAN ZONASI TERHADAP KUALITAS PENDIDIKAN DI SMP NEGERI 4 COMAL KABUPATEN PEMALANG - Iman Ningrum, Lela; Ardiani, Tika; Nurkolis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study analyzes the impact of zoning policy on the quality of education at SMP Negeri 4 Comal, Pemalang Regency. The zoning policy was introduced to improve equitable access and quality of education, where students are accepted based on their proximity to the school. A qualitative approach with a descriptive method was employed, involving observations, interviews, and documentation from the principal, teachers, students, and parents. The findings indicate that the implementation of the zoning policy at SMP Negeri 4 Comal has improved educational access; however, challenges remain, such as inadequate infrastructure and community resistance related to perceptions of favored schools. This research provides recommendations for local governments to enhance the implementation of zoning policies to effectively achieve equitable educational quality. Thus, this study contributes to the development of public administration knowledge, particularly in the context of educational policy in Indonesia. Keywords: zoning policy, quality of education, SMP negeri 4 comal